أثر العائد الاقتصادي للتعليم في سورية في التنمية الاقتصادية - الرفاعي, عبد الهادي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
مازال ميدان اقتصاديات التعليم من الميادين البكر نسبياً، فقد ظل رجال الاقتصاد زمناً طويلاً يغفلون دور التعليم كعامل أساس في التنمية الاقتصادية، و ذلك لصعوبة قياس العائد الاقتصادي للتعليم بشكل دقيق كالمشروعات الاقتصادية الأخرى. لذلك حاولنا في هذا البحث تعريف العائد الاقتصادي للتعليم و بيان مؤشرات الحالة التعليمية المؤثرة على العائد الاقتصادي للتعليم باستخدام التحليل العاملي و التحليل القانوني، و من ثم حاولنا بيان أثر العائد الاقتصادي للتعليم على التنمية الاقتصادية في سورية. حيث توصلنا إلى تحديد أهم متغيرات التركيب القانوني U1 الذي تم اختياره ليمثل المتغيرات التعليمية، و كذلك قمنا ببناء النموذج القانوني لمعرفة أثر U1 في التركيب القانوني V1 الذي تم اختياره ليمثل متغيرات التنمية الاقتصادية. Economics of education domain is still considered as a relatively small domain since most economists did not consider employing education within the main factors of economical development due to the difficulty in measuring the economical return of education precisely comparing to other economical projects. thus we tried within this study to identify the economical return of education as to demonstrate the indicators of education that affects the economical return of education by using both factor and canonical analysis. then we tried to demonstrate the impact of economical return of education on the economical development within Syria. In conclusion we were able to determine the variables of the canonical compositions U1 which has been set to represent the educational variables، as we were able to build the canonical model to identify the effect of U1 on the canonical compositionV1 which has been set to represent the variables of economical development.